Comparing verbal and visual representations of grade-9 natural sciences concepts, constructs, and principles of matter and materials in three textbooks and the CAPS policy document - Mofolo, Serapelo Boipelo Oreeditse; Rabaza, Msebenzi (Frontiers in Education, 2025)
Due to the freedom afforded natural sciences textbook authors globally and in South Africa, there are verbal and visual misrepresentations of matter and material concepts, constructs, and principles globally, and in South Africa. These misrepresentations may negatively affect the way teachers teach and learners learn natural sciences content, though there are policy frameworks that guide the development of textbooks for secondary school, especially for grade-9. One asks why this is the case when several modes of representation are used in natural sciences textbooks to explain the natural sciences concepts, constructs, and principles aligned to the Curriculum Assessment policy Statements (CAPS) document. The textbooks can use verbal or visual representations or a combination of them. Verbal representation (VeR) of subject matter in textbooks comprises definitions, descriptions, explanations, and step-by-step methods while visual representations (ViR) may include drawings, graphs, and models. The verbal aspects are presented in more detail in textbooks than in curriculum assessment policy statements (CAPS) documents. The ViR (images) are only discussed in the CAPS document and no images are provided. These differences between textbooks and the CAPS document may pose a challenge to natural sciences teachers, especially novice teachers who seek guidance from the textbook rather than analysing the CAPS document to prepare and present a lesson on matter and materials.